2015
DOI: 10.1371/journal.pone.0122831
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 2848 GA Heterozygotic Status Possibly Predisposes Fetuses and Newborns to Congenital Infection with Human Cytomegalovirus

Abstract: BackgroundSome single nucleotide polymorphisms (SNP), located in Toll-like receptor (TLR) genes, were reported to be associated with human cytomegalovirus (HCMV) infections. The study was aimed to assess the correlation of SNPs at TLR4 and TLR9 genes with the occurrence of congenital cytomegaly, based on available samples.MethodsReported case-control study included both HCMV infected and non-infected fetuses and newborns. The specimens were classified to the molecular analyses, based on serological features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…Associations between TLR2 [16, 17], TLR4 [18], and TLR9 polymorphisms [19–22] with HCMV infection have been found. It was previously demonstrated that the TLR9 –1486 and 2848 polymorphisms as well as the TLR2 1350 SNP are associated with an enhanced risk of HCMV infection and disease in newborns and infants [2325]. However, little is known about the role of TLR3 and TLR7 polymorphisms in the pathogenesis of cytomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between TLR2 [16, 17], TLR4 [18], and TLR9 polymorphisms [19–22] with HCMV infection have been found. It was previously demonstrated that the TLR9 –1486 and 2848 polymorphisms as well as the TLR2 1350 SNP are associated with an enhanced risk of HCMV infection and disease in newborns and infants [2325]. However, little is known about the role of TLR3 and TLR7 polymorphisms in the pathogenesis of cytomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the analyzed polymorphism was suggested to participate in the development of HCMV disease in humans [23]. Other studies also showed the SNPs located in TLR2 , as well as in TLR3 , TLR4 , TLR7 and TLR9 genes, to be contributing to HCMV infection [13, 14, 27]. So far, no study has shown any relationship between genetic alterations in TLR2 2258 G>A SNP and congenital HCMV infection.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a possible contribution of TLR4 and TLR9 SNPs to congenital cytomegaly [14]. These recently published outcomes, as well as the available literature data on the contribution of TLR2 SNPs to the occurrence of HCMV infection, prompted us to undertake further research, evaluating the role of TLR2 1350 T>C coding synonymous (Ser450, rs3804100), as well as 2029 C>T (Arg677Trp, rs121917864) and 2258 G>A non-synonymous (Arg753Gln) SNPs in the development of HCMV congenital infection in fetuses and neonates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations